2019
DOI: 10.14744/nci.2018.90922
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of ankylosing spondylitis and discoid lupus: A case report

Abstract: Coexistence of ankylosing spondylitis with connective tissue diseases is very rare. Here, in this study, we describe a coexistence of ankylosing spondylitis and discoid lupus erythematosus in a 35-year-old man. He presented with a 5-year history of low back pain and concurrent development of a discoid rash. Inflammatory low back pain, HLA-B27 positivity and bilateral active sacroiliitis confirmed the diagnosis of ankylosing spondylitis. Discoid lupus erythematosus was diagnosed based on a skin biopsy. There ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Thus, there have been reports of a variety of inflammatory skin responses such as erythema elevatum diutinum, discoid lupus and other vasculitides in patients with AS. [229][230][231] Pathomechanistically, they all seem to share a common pathway, with dysregulation of classic inflammatory cytokines such as IL-1, IL-12/23, IL-17 and IL-23. Common genetic factors like HLA-B27 are also typical in these cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there have been reports of a variety of inflammatory skin responses such as erythema elevatum diutinum, discoid lupus and other vasculitides in patients with AS. [229][230][231] Pathomechanistically, they all seem to share a common pathway, with dysregulation of classic inflammatory cytokines such as IL-1, IL-12/23, IL-17 and IL-23. Common genetic factors like HLA-B27 are also typical in these cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…4 In 2019, Enginar reported a case of spondyloarthritis with discoid lupus, with manifestation of both disorders at the same time of presentation. 5 Another case was reported by Tarhan in 2014, where a patient of SLE (biopsy-proven lupus nephritis) presented with spondyloarthritis manifestations 8 years after diagnosis of SLE. 7 Here the time frame may be comparable to the currently documented second case, but the patient was a young male who was diagnosed initially with lupus and diagnosed with spondyloarthritis after 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…SLE usually develops as nonerosive arthritis; however, rhupus arthritis could be erosive as seen in the present study [ 20 ]. In another study, Benavente presented the clinical and serological characteristics of four rhupus patients [ 22 ]. They fulfilled ACR criteria for SLE and RA: ANA positive with titers ranging from 1/80 to 1/5250 and anti-ds-DNA, anti-CCP (3/4), and positive antiphospholipid antibodies in two patients (anticardiolipin and lupus anticoagulant) without manifestation APS.…”
Section: Discussionmentioning
confidence: 99%
“…One patient presented renal affection and 2 with subcutaneous nodules. Two patients were refractory to conventional DMARD and required biologics and mycophennolate mofetil [ 22 ]. Fernández et al reported eight patients with rhupus arthropathy; among them, three had erosive arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation